Improving Islamic Students’ Ability on Mastering Names and Responsibilities of Angels through Word Guessing Game - Yosmiza Yusra (AT-TA'LIM, 2017)
From the researcher's experience in the field, many students were reluctant to ask for any clarification, unwilling to express their opinion, less able to give feedback, and did disruptive behaviors during the learning process. Ideally, students are expected to be active and involved in the learning process and to get good learning outcomes. This study is a Class Action Research (CAR), which attempts to improve students' activity and learning outcomes. The research was conducted through four main stages: planning, implementation, monitoring, evaluation and reflection. The research findings from teaching the names and responsibilities of angels through the classical method do not obtain maximum result. On the other hand, word guessing learning model shows better results than that of the classical one. In this model, students are motivated to compete with one another in making and answering the questions. The normally passive students are encouraged to participate actively in learning. Thus, it can be concluded that the learning process with of the game will improve students' learning outcomes